The Idea of Inclusive Growth and Development Policy - Naqvi, Syed Nawab Haider (International Food Policy Research Institute, 2012)
The evolution of development policy over time can be characterized as a faltering pursuit of inclusive growth: namely, an integrated program of achieving highest possible rate of growth of the real GDP that doubles per capita income within a short period of time, with an eye on distributive justice and an undivided focus on reduction in poverty. There is a link that ties these apparently disparate policy objectives; but these links need to be strengthened by deliberate government policy to make them fully functional.2 It is only by achieving these connected objectives simultaneously or in quick succession that efforts to bring prosperity to humanity condemned perpetually to a life of drudgery and poverty can be crowned with suc-cess.3 The greatest minds in economics from Physiocrats to modern times have addressed this problem. Yet it remains an unfinished agenda of human existence--- equivalent to the mathematical problem of “squaring the circle”. It is, therefore, apt that the success of a set of development policies is judged by reference to the fulfilment or non-fulfilment of this universally valid amorphous objective---it is universally valid because it is a relevant reckoner regardless of state of development of a society. However, a successful pursuit of this agenda is a non-trivial exercise; but it is by no means impossible.